Estimating past and future male loss in three Zambian lion populations1. Issue 1 (23rd August 2012) - Becker, Matthew S.; Watson, Fred G.R.; Droge, Egil; Leigh, Kellie; Carlson, Ron S.; Carlson, Anne A.
Abstract African lions (Panthera leo) are declining continent‐wide, with protected area populations subject to a variety of anthropogenic effects. Zambia contains viable lion populations of considerable importance for photographic and hunting tourism, but long‐term lion demographic data do not exist to guide recent management directives and population projections under different strategies. We described population size, as well as age and sex structure of lions in 3 Zambian national park populations bordering hunting areas, and found them to be male‐depleted relative to other systems. We then estimated rates of adult male loss leading to male depletion in these populations and the effect of different future hunting management options on population characteristics. Predictions from matrix population models constructed within a Bayesian framework confirmed that the observed population structure was likely due to high rates of adult male loss and that instituting age limits on male harvests with quota reductions would reduce male depletion, improve tourism by providing older and more abundant males, and slightly increase population size. Reducing male mortality from wire snare poaching would also result in similar demographic impacts, and in concert with changes in hunting regulations would substantially improve the quality and quantity of adult male lions. However, model results varied depending on whether we assumed historical population stability. Predictions assuming negative historical growth rate indicated that substantially more conservative lion harvest management is warranted. We discuss the relevance of these findings for maintaining viable lion populations in and around protected areas in Zambia. © 2012 The Wildlife Society.